Internalization of Religious Tolerance Values Through “Forum Kerukunan Umat Beragama” Batu City - Ibda Wahyu Setiana; M. Lutfi Mustofa; Badruddin Badruddin (Universitas Negeri Padang, 2022)
The population census data for 2021 recorded that there were six beliefs spread throughout Indonesia Tolerance is an important thing for all people to do. Batu City as one of the cities with a pluralistic religious background has long fostered brotherhood with tolerance. This culture is a concern for religious harmony forums to continue to maintain and preserve the culture of tolerance. Examples of tolerance behavior that has been implemented are the existence of a culture of mutual cooperation in the construction of places of worship, religious activities which are also attended by followers of other religions, to the formation of a village aware of religious harmony located in Mojorejo district. Junrejo. This type of research is field research with a qualitative approach. The theory of social construction as an analytical tool regarding the internalization of the value of religious tolerance, the religious harmony forum of Batu city. Based on research activities with the process of collecting data through interviews, observations and interviews. As a result, there is a doctrine from the family and a forum for religious harmony in Batu city regarding tolerance, then the religious harmony forum as an institution authorized to manage harmony has the same ideas and perspectives on tolerance between religious communities. Keywords: Tolerance, Forum Kerukunan Umat Beragama, Batu City